Amines as key building blocks in Pd-assisted multicomponent processes - Bouyssi, Didier; Monteiro, Nuno; Balme, Geneviève (Beilstein Journal of Organic Chemistry, 2011)
In the last few years, palladium-mediated three-component synthesis has emerged as an important synthetic methodology to gain access to nitrogen-containing structures. The latest developments in this area are discussed in this review.
Keywords: amines; multicomponent reactions; palladium